Keterampilan Mengadakan Variasi - Faelasup Faelasup; Eka Wahyuni (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2026)
A teacher's ability to make deliberate adjustments to the learning process to reduce boredom, increase student attention, and maintain learning motivation is known as the talent of offering variety. Through a literature survey, this study seeks to characterize and evaluate the ability to provide variety as one of the fundamental teaching qualities of a teacher. This study uses a qualitative methodology and library research strategy. Secondary data from books, journals, previous research, and other relevant sources are the sources of data used in this study. The results of the study showed that the increase in teacher skills in providing variations—which include variations in teaching styles, variations in the use of learning media, and variations in interaction patterns—was directly proportional to the increase in student focus. Student learning activities increased from [X]% in cycle I to [Y]% in cycle II. In line with this, the classical completeness of student learning outcomes also increased significantly by [Z]%. Based on these results, it can be concluded that the effective application of variation skills can reduce student boredom, increase active involvement in class, and optimize learning outcomes. The study findings indicate that the use of this skill improves learning outcomes and educational standards in general by increasing student understanding, learning interest, concentration, and participation.